Ganoderma lucidum in an animal model of obesity: preliminary results - Martins, Tiago (2021)
Obesity is an emerging health problem worldwide. Hypercaloric or hyperlipidemic diets have been used as models of obesity induction in laboratory animals. Obesity can be influenced by regular consumption of natural bioactive compounds. Mushrooms, such as Ganoderma lucidum (GL), have been used in the human diet since ancient times and include a wide variety of biomolecules with medicinal properties. The main objective of this work was to study the effects of G. lucidum in an animal model of obesity.